Evaluation of the intensity of helminth infection of calves using equations of regression - Freitas, Moacyr G.; Costa, Hélio M.A.; Lima, José D. (Pesquisa Agropecuaria Brasileira, 2014)
The data used in the experiment were based upon helminth counts found in postmortem examination of 150 calves of mixed breeding, naturally infected with helminth parasites. Using the mean counts of helminths, found in sections of the gastrointestinal tract of calves, regression analyses were made from which equations were determined for estimating the total worm burden for groups of calves. Equations of regression are presented to calculate the intensity of the infection of Haemoncus spp., Trichostrongylus axei, Cooperia spp., Bunostomum phlebotomum, Strongyloides popillosus, Trichuris discolor and Oesophagostomum radiatum.